Estrategias de Merchandising en la Empresa Los Paisas Grupo JG sucursal Babahoyo periodo 2023. - Paredes Cabello, Jhors Mauricio (2025)
The subject deals with the merchandising tactics that the company Los Paisas Grupo JG applied in its Babahoyo subsidiary during 2023. Merchandising refers to the set of methods used to optimize the sale of products, through their adequate display, distribution and promotion at the point of sale. In this scenario, the company implemented several strategies aimed at increasing the visibility of its products, capturing consumer attention and promoting impulse purchases. The tactics include the correct placement of products on shelves, the use of advertising, special offers and the optimization of space in the establishment to make it more attractive and easier to reach. These strategies are designed to impact consumer behavior and boost the subsidiary's sales.